2012
DOI: 10.1080/08952833.2012.629130
|View full text |Cite
|
Sign up to set email alerts
|

Negative Perceptions of Never-Married Custodial Single Mothers and Fathers: Applications of a Gender Analysis for Family Therapists

Abstract: In this study the authors examined perceptions of the negative attributes of never-married, custodial, single mothers and fathers and applied a feminist framework to determine what gender-based differences existed in these perceptions. Data were collected from 769 participants who were randomly assigned to answer questions about single mothers or fathers. The results of the thematic analysis suggested that participants' perceptions of single mothers and fathers varied primarily by the gender of the single pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…Similar findings are reported across the globe [11]. In this study, some other factors such as desires of female parents for economic independence, career and lack of patience in marriage are also believed to have attributed to the increasing rates of single-parenthood (as shown in Table 2).…”
Section: Awareness and Knowledge Of Single Parentingsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar findings are reported across the globe [11]. In this study, some other factors such as desires of female parents for economic independence, career and lack of patience in marriage are also believed to have attributed to the increasing rates of single-parenthood (as shown in Table 2).…”
Section: Awareness and Knowledge Of Single Parentingsupporting
confidence: 73%
“…This finding is similar to what Allers [6] described as "a single-mother hierarchy" in her article on single parenting. Hence, some authors have also reported that loss of spouse gets public sympathy [11] and some single parents find themselves in it unplanned for, such as in broken relationship [4]. This opinions makes support a social decision.…”
Section: Awareness and Knowledge Of Single Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with existing research that has explored societal perceptions toward married and nevermarried parents and consistently found that single parents are viewed more negatively than any other group of parents (Bryan, Coleman, Ganong, & Bryan, 1986;Ganong, Coleman, & Riley, 1988;Rhodes & Johnson, 2000;Usdansky, 2009b). While negative societal perceptions of single parents as a group have been well-documented, the research also suggests that these perceptions vary by the gender of the single parent (Bennett & Jamieson, 1999;Bryan et al, 1986;Haire & McGeorge, 2012;Hilton & Devall, 1998). In particular, researchers argue that single mothers are viewed more negatively than single fathers (DeJean et al, 2012;Ganong et al, 1988;Hilton, Desrochers, & Devall, 2001;Jarrett, 1996).…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, if therapists were better aware of the perceived societal strengths of single parents this might make visible the competent and impressive parenting that many single parents provide. Finally, researchers have documented that negative societal beliefs about single parents appear to vary by gender (Bennett & Jamieson, 1999;DeJean et al, 2012;Haire & McGeorge, 2012). Thus, we postulated that the positive perceptions about single mothers and fathers may differ as well.…”
Section: Introductionmentioning
confidence: 92%